Organisation of Social Art in Performance Art Organisations - Kyguolytė-Kataržė, Irena; Jurėnienė, Virginija (Vilnius University Open Series, 2021)
Art as a social action in the public space is becoming more popular in various forms, especially in the digital space, and especially after the recent events that have had an effect on the whole world. However, theatre as art is changing its forms of accessibility not only due to global events but also due to the changing society from various aspects, i.e., psychological, social, economic, political, etc. The article provides a comparative analysis of the concepts of social art actions and performance art, presents the features of social art actions organisation in performance art organisations in Lithuania and abroad, determines the impact of social art action on human health from the psychosocial and spiritual point of view as well as in a community; it also provides a discussion of similarities and differences of performance as not only theatre but also performance art and social art, social art actions as performance art. Moreover, the article analyses how performance is compared to social art performance, how spectator and participant audiences manifest, what inclusion of performance art as a social art action into human spiritual-psychological space provides. The article provides an analysis of how performance art cooperates with performance art organisations.